Exploring Students’ Critical Thinking through Flipped Classroom Approach in Chemistry Learning at Penang Straits International School - Hamid, Abdul; Rahmad, Ashror (Lembaga Publikasi Ilmiah Nusantara, 2025)
The cultivation of critical thinking skills has become a fundamental objective in 21st-century education, particularly in science subjects such as chemistry. This study aims to explore the effectiveness of the flipped classroom approach in fostering students’ critical thinking during chemistry learning at Penang Straits International School. Utilizing a qualitative descriptive research design, the study involved 30 Year 10 students enrolled in a chemistry course. Data were collected through classroom observations, student interviews, and performance assessments, focusing on students’ ability to analyze, evaluate, and synthesize information. The flipped classroom model, which inverts traditional teaching by delivering instructional content online outside of class and engaging students in interactive activities during classroom sessions, was implemented over a six-week period. The findings revealed that students exhibited significant improvement in critical thinking indicators, especially in problem identification, argument construction, and logical reasoning. Students also reported increased motivation and deeper conceptual understanding due to the active learning environment facilitated by the flipped approach. Teachers observed that students were more prepared and willing to engage in higher-order thinking tasks. This study concludes that the flipped classroom approach is a viable and effective pedagogical strategy for enhancing critical thinking in chemistry learning. The results suggest that integrating technology with active learning frameworks can transform traditional classrooms into dynamic learning environments that promote cognitive development.